Factors Associated to The Use of Iodized Salt by Housewives in Kecamatan Mila Kabupaten Pidie in 2020 - Ramadhaniah Ramadhaniah; Juwita Juwita; Fauzi Ali Amin; Afwa Hayuningtyas (Journal of Nutrition Science, 2021)
To improve the nutritional quality of individuals and communities through improving consumption patterns, it could be obtained by the achievement of household nutrition indicators in Kecamatan Mila Kabupaten Pidie. The intensity of households consuming iodized salt has decreased by year in 2017 (51%), 2018 (44%), and 2019 (31%). This condition resulted in 10 person having disorders due to iodine deficiency, 9 of them suffering goiter and 1 person suffering thyroid disease. The purpose of this study was to determine the factors associated with the use of iodized salt by housewives in Kecamatan Mila, Kabupaten Pidie in 2020. This study used a cross-sectional analysis method. The result showed that based on univariate analysis family knowledge and support were the most related variables with the use of iodized salt, while the health education variable (1.00) has no significant relationship with the use of iodized salt (p-value = 0.00).